Chemometrics as analytical tool for definition of the conditions of assay of soybean peroxidase - Santos, M. C. [UNESP]; Tognolli, J. O. [UNESP]; Oliveira, O. M.M.F. [UNESP] (Ecletica Quimica, 2010)
Peroxidases enzymes are heme-proteins found in the different organisms livings creature, especially vegetal, present in important physiological paper/biochemist as protection against microorganisms. The soy, one of the most important products for the Brazilian agribusiness, presents in the rind of its seeds (byproduct) where has high activity of peroxidase, called soybean peroxidase, with potential of use in clinical analytical methods. The proposal of the work was to apply the factorial planning for optimization of the conditions extraction of this enzyme, definition of the conditions of kinetic-enzyme assay conditions (pH and temperature), using methodology of reply surface. The data obtained: i) extraction in cetonico power, ii) reactional medium: pH 3,3, volume of the sample contend enzyme 330 μL - 340 μL, hydrogen peroxide 4,2 mmol.L-1150 μL, time of reaction 20 seconds, temperature 50º C, substrate guaiacol 30mmol.L-1300 μL, and 0.1 mol.L-1of NaCl. This chemometric methodology used to definition of the extraction conditions and parameters kinetic assay of soybean peroxidase was very efficient, compared the classical methodology of variations/repetitions (attempt and error).
Quimiometria como ferramenta analitica para definiÇÃo das condiÇoes de ensaio da enzima peroxidase de soja
Keywords: Enzyme extraction; Kinetic parameters; Optimum pH; Optimum temperature; Soybean peroxidase